2022
DOI: 10.5603/fm.a2021.0073
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of bone marrow-derived mesenchymal stem cell transplantation in a D-galactose-induced brain aging in rats

Abstract: Aging is a complex process accompanied by numerous morphological, functional, and metabolic impairments in the brain, and a critical risk factor involved in the increasing incidence of neurodegenerative diseases. Few studies have evaluated the efficacy of different sources of mesenchymal stem cells (MSCs) in ameliorating the early morphological and functional alterations in the aging brain. This study, for the first time, evaluated the potential efficacy of intravenous injection of bone marrow-derived mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…Several studies have shown that the DA system, both structurally and functionally, is affected during normal ageing [1][2][3][4][5][6][7][8]. The capability of stem cells to replace lost or malfunctioning cells has been the focus of recent research [36][37][38][39][40][41][42]. This study is the first to examine the potential beneficial effects of systemic transplantation of BMMSCs on the DA system in a D-gal-induced rat model of brain ageing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the DA system, both structurally and functionally, is affected during normal ageing [1][2][3][4][5][6][7][8]. The capability of stem cells to replace lost or malfunctioning cells has been the focus of recent research [36][37][38][39][40][41][42]. This study is the first to examine the potential beneficial effects of systemic transplantation of BMMSCs on the DA system in a D-gal-induced rat model of brain ageing.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that early intervention to address neuropathological changes during primary ageing will stop or at least delay the pathological processes leading to secondary ageing, thus lowering the prevalence of agerelated disorders [19][20][21][33][34][35]. Few studies have evaluated the efficacy of MSC transplantation in animal models of ageing [36][37][38][39][40][41][42]. Therefore, we aimed to evaluate, for the first time, the potential beneficial effects of systemic transplantation of BMMSCs on the nigrostriatal system in a D-galactose (D-gal)-induced rat model of brain ageing to evaluate their potential as a protective approach for age-related neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%